2006
DOI: 10.1103/physrevb.73.094203
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature order-disorder transition and polaronic conductivity inPrBaCo2O5.48

Abstract: Neutron powder diffraction and transport measurements have been used to investigate the PrBaCo 2 O 5.48 compound between room temperature and 820 K. A structural phase transition, involving a rearrangement of oxygen vacancies, was found at T OD = 776 K. Across the transition the perovskite structure loses its vacancy ordering, and the crystal symmetry changes from orthorhombic Pmmm to tetragonal P4/mmm. The resisitivity measurements for temperatures above ϳ350 K yield high values of , indicating that the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 34 publications
6
44
0
8
Order By: Relevance
“…The parameter (5+δ) varies from 5.2 to 5.55 within the studied limits of T and pO 2 . When heated in He the cobaltite acquires tetragonal structure (S.G. P4/mmm) [25] with δ¼ 0.48 at 503 1С. Similar structural transition near 500 1С was observed also in other rare-earth cobaltites LnBaCo 2 O 5+δ , where Ln¼ Nd, Sm, Gd [26,27].…”
Section: Defect Equilibrium Modelmentioning
confidence: 51%
See 2 more Smart Citations
“…The parameter (5+δ) varies from 5.2 to 5.55 within the studied limits of T and pO 2 . When heated in He the cobaltite acquires tetragonal structure (S.G. P4/mmm) [25] with δ¼ 0.48 at 503 1С. Similar structural transition near 500 1С was observed also in other rare-earth cobaltites LnBaCo 2 O 5+δ , where Ln¼ Nd, Sm, Gd [26,27].…”
Section: Defect Equilibrium Modelmentioning
confidence: 51%
“…2 (pO 2 -Т-δ diagram) pertain to tetragonal phase modification of PrBaCo 2 O 5+δ . The smooth shape of the isotherms gives additional evidence to the absence of phase transitions in PrBaCo 2 O 5+δ within the studied range of oxygen pressure and temperature values; the stability of tetragonal structure at elevated temperatures is due to randomization of oxygen ions O 2-and vacancies V O over O3 positions [25][26][27]. Simple consideration of charge balance suggests coexistence of Co 2+ and Co 3+ cations mostly in PrBaCo 2 O 5+δ at δo0.5.…”
Section: Defect Equilibrium Modelmentioning
confidence: 88%
See 1 more Smart Citation
“…The E a of R LF is reduced from 96 kJ mol ±1 at 500±600 C to 51 kJ mol ±1 at 650±750 C. This range of higher temperatures shows an oxygen nonstoichiometry of d < 0.27 (Figure 6b). According to the previous reports, the oxygen vacancies are mainly located at Ln-O x planes (d in the range of 0±0.5) [48]. The oxygen conductivity of EBCO will increase as generating new oxygen vacancies until a maximum of oxygen nonstoichiometry (d = 0.27 at 650 C), then will decrease with further increasing oxygen vacancy concentration due to the incorporation between oxygen vacancy and negative defects (Ba¢ Eu ).…”
Section: Cathode Microstructure and Electrochemical Performancementioning
confidence: 93%
“…Among the various PrBaCo 2 O 5+δ with different oxygen content (δ), ordering of the oxide- [40,41] ion vacancies in the Pr-O layers was observed for the samples with δ~0.75 and 0.5, and the oxide-ion vacancy ordering was found to be lost for δ~0.87 and 0.18 at room-temperature. Additionally, Streule et al [52] have reported the effect of heating on the oxide-ion vacancy order-disorder transition in PrBaCo 2 O 5. 48 .…”
Section: Abo 3 Perovskite Oxidesmentioning
confidence: 98%